Internet addiction and related factors among high school students in Vietnam - Nguyen, Thao; Nguyen, Nguyen; Pham, Nhan Hong; Tran, Ly Cong; Tran, Nghia; Nguyen, Dat Tan (Annali di Igiene Medicina Preventiva e di Comunità, 2026)
Background: Internet addiction has emerged as a widespread concern, particularly among adolescents. Despite this growing issue, there is a scarcity of empirical data regarding the socio-demographic factors of internet addiction among high school students in Vietnam. Therefore, this study aimed to investigate the extent of internet addiction and its associated factors among Vietnamese high school adolescents.Methods: This analytical cross-sectional study was conducted from February to March 2025 among Vietnamese high school students. Internet addiction was assessed using the Internet Addiction Test – Short Version (IAT-SV), alongside data on demographics, academic performance, and psychosocial factors. Statistical analyses, including independent t-tests, one-way ANOVA, Post-Hoc Test, and multiple linear regression, were applied to explore differences between these variables and internet addiction.Results: A total of 789 students participated in the study, with a mean IAT-SV score of 28.79 (SD = 9.41). Female students (M = 29.84) and older students (M = 30.24) exhibited significantly higher internet addiction scores. Similar trends were observed among students with a family history of psychological disorders (M = 32.48) or smoking addiction (M = 31.22). Higher internet addiction scores were also found among students from families with difficult or very difficult economic conditions (M = 32.37), those reporting lower levels of happiness (M = 33.16), and those who perceived their academic environment negatively (M = 33.59). In contrast, lower scores were observed among male and younger students, those without such family histories, from families with moderate economic status, who reported being happy or very happy, and who viewed their academic environment positively. The regression model was statistically significant and accounted for 7.4% of the variance in internet addiction scores.Conclusion: Several factors are associated with internet addiction. Notably, fostering a supportive academic environment and enhancing students’ overall well-being and happiness may contribute to reducing the prevalence of internet addiction. Further research is warranted to explore effective strategies for addressing internet addiction among adolescents.